Physiological responses and production of Gama Melon Parfum (Cucumis melo L. cv. GMP) on different water availability - Nellis Nadinda Putri Renata; Budi Setiadi Daryono; Wiko Arif Wibowo; Diah Rachmawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Gama Melon Parfum (GMP) cultivar is a result of crossbreeding between the Natsuno Omoide and Miyamauri melon varieties in 2011. GMP exhibits a unique phenotypic characteristic, including a bitter taste of the fruit flesh and produces a stronger aroma. The objective of this study was to investigate the physiological responses and productivity of GMP under varying water conditions. The experiment was conducted using a single factor consisting of different levels of water availability with field capacity at 50%, 75%, and 100%, as well as submergence at 2 cm, 4 cm, and 8 cm above the soil surface. Each treatment was replicated three times. The plot size for each replication was 2 m x 2 m, ensuring consistent conditions for all treatments. The results of the study showed that treatment with 100% field capacity increased stem diameter, while treatment with 50% field capacity increased the root-to-shoot ratio of GMP. Submergence treatment at 8 cm decreased stem diameter and the root-to-shoot ratio of GMP. The 50% field capacity treatment reduced the total chlorophyll levels in GMP leaves. Submergence treatment at 8 cm increased the total chlorophyll levels in GMP leaves. The 50% field capacity treatment increased fruit fresh weight, while submergence treatment at 2 cm decreased fruit fresh weight. Submergence treatment at 2 cm reduced fruit water content, whereas submergence treatment at 8 cm increased water content in GMP fruits. Keywords: drought; Gama Melon Parfume (GMP); growth; plant physiological responses; submergence